TANGGUNG JAWAB PELAKU USAHA DALAM MEMBERIKAN INFORMASI MENGENAI MEREK YANG MEMILIKI PERSAMAAN PADA POKOKNYA STUDI KASUS MEREK I AM GEPREK BENSU DENGAN GEPREK BENSU DI KOTA BUKITTINGGI - Zahara, Maya; Firdaus, Firdaus; Dasrol, Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Problems that often occur in brands are brand holders who have similarities between one brand and another that has been registered. The condition of consumers who are harmed a lot, requires efforts to protect them, so that consumer rights can be upheld. Therefore, business actors are respondible for providing correct, clear and honest information to consumers regarding the similarities between their brands and other brands so that consumers are not mistaken or feel cheated and do not harm the interests of consumers and are responsible for consumer rights to create a competitive climate healthy and honest business.The purpose of this study is to determine the responsibility of business actors in providing information about brands that have similarities in essence, a case study of the I Am Geprek Bensu brand with Geprek Bensu brand in Bukittinggi city and to find out what efforts consumers can do to protect their rights by using sociological legal research methods can be concluded that First, there is still a lack of implementation of the responsibilities of business actor I Am Geprek Bensu brand and Geprek Bensu brand in providing information about the two brands that have the same basic principle in using the word BENSU. This is the same as a result that many consumers are mistaken and disadvantaged because it is possible that what they buy is not the food product they really want. Second, efforts that consumers can take to protect their rights can be started by raising awareness within themselves of the importance of the rights of consumers. then consumers must be careful before buying a product, read the information listed on a product, think critically and don’t be easily persuaded when hearing promotions and discounts on a product, look for information about a product if the existing information is not sufficient,dare to ask employees/busoness actors of a product to ensure and obtain clearer and definite information about a product.Keywords: Responsibility-Business actor-brand-I Am Geprek Bensu- Geprek Bensu